Upaya Meningkatkan Penjualan dan Laba pada UMKM Melalui Penerapan Strategi Pemasaran 4.0 (Studi pada Warunk Dejavu Jember) - Susanti, Indria Yuli; Syaifullah, Rama (ACCOUNT (Journal of Accounting and Finance), 2024)
Efforts to increase sales and profit achievements for an entity can be done in various ways, one of the efforts made by Warunk Dejavu is to increase profits by implementing a renewable marketing strategy, namely marketing strategy 4.0 which combines offline and online marketing strategies. The aim of this research is to analyze Warunk Dejavu's efforts to increase its sales volume and profit through implementing marketing strategy 4.0. The research results show that after implementing marketing strategy 4.0 with 4C marketing elements, namely co-creation, currency, communal activation, and conversation, sales increased by 15% to 20%, while profits increased by 20% to 25%.